Capitolunate Arthrodesis versus Four-corner Arthrodesis in Scaphoin Nonunion Advanced Collapsed Wrist Treatment - González Porto, Sara Alicia; Cano Leira, María Ángeles; González Rodríguez, Alba; Álvarez Jorge, Ángel (Revista Iberoamericana de Cirugía de la Mano, 2019)
Objective To evaluate the outcomes of scaphoidectomy and capitolunate arthrodesis versus four-corner arthrodesis in patients with stage III scaphoid nonunion advanced collapse (SNAC) wrists.Methods We reviewed retrospectively all of the consecutive patients surgically treated in our center between 2007 and 2015, including 20 patients in the four-corner arthrodesis group and 11 patients in the capitolunate group. The mean follow-up time was of 47 months. The follow-up evaluation included wrist range of motion (ROM), grip strength, visual analogue scale (VAS), the disabilities of the arm, shoulder, and hand (DASH) questionnaire, and the Mayo wrist scale (MWS). Postoperative complications and the radiographic evaluation were also assessed.Results There was no statistical difference in flexion, radial deviation, ulnar deviation, grip strength, VAS, DASH or MWS scores. There was a statistically significant increase (6°) in extension in capitolunate arthrodesis versus four-corner arthrodesis, possibly without clinical relevance. There were two nonunions in the four-corner group, and none in the capitolunate group. None of the patients in the capitolunate group required screw removal. One patient in the four-corner group required dorsal plate removal. One patient in each group required conversion to total arthrodesis.Conclusions Capitolunate arthrodesis shows similar results in wrist ROM, grip strength and patient-reported outcomes when compared with four-corner arthrodesis at an average follow-up period of 4 years. We did not have any pisotriquetral arthritis in the capitolunate arthrodesis group, despite not removing the triquetrum in any of patients of this group.Type of study/level of evidence Therapeutic III.
Keywords: arthrodesis; four-corner arthrodesis; capitolunate; fusion; wrist